INDONESIAN NURSES' EXPERIENCES WORKING IN AURORA, COLORADO: A PHENOMENOLOGICAL STUDY - Serly Vinanda Jenne; Evelyn Hemme Tambunan (Universitas Kadiri, 2025)
This phenomenological study explores the lived experiences of Indonesian nurses working in Aurora, Colorado. The study aims to understand the multifaceted aspects of their professional and personal lives, focusing on financial well-being, mental well-being, relationships with coworkers, and perceptions of the personnel system. Utilizing in-depth interviews, the study captures the essence of their experiences, revealing both challenges and opportunities encountered in navigating a foreign healthcare system and culture. The findings illuminate the four themes including “The Promise and the Reality, “Stress, Support, and Resilience,” Navigating Cultural Differences and Building Bridges,” and “Career Paths, Work-Life Balance, and Opportunities for Growth.” The study contributes to a deeper understanding of the global nursing migration phenomenon and offers valuable insights for improving the integration and support of international nurses in the United States healthcare system.